Analisis Tataniaga Sawi di Kecamatan Liang Anggang Kota Banjarbaru - Nopri Adiansyah; Abdullah Dja'far; Rifiana Rifiana (Universitas Lambung Mangkurat, 2013)
Currently, the price of Chinese cabbage is highly fluctuated. It not only causes the instability of farmer income and community consumption, but also increases the marketing risk and creates marketing channel problem. In this regards, the study about marketing channel is essential. Thus, the purposes of the study are: (1) to trace the marketing channel of Chinese cabbage in Kot a Banjarbaru, (2) to estimate the price margin, cost, and profit on each channel, (3) to calculate the price share of each farmer and the parties involved, (4) to analyze the channels efficiency, and (5) to identify the problem encountered in the product transferring process. The marketing channel costs consist of transport, risk guarantee, market fee, cleaning, loading, and packaging cost. On the study site, two main channels are traced, i.e.: (1) farmer - 1st level trader/retailer - consumer; and (2) farmer - 1st level trader - retailer - consumer. The first channel is technically and economically more efficient that the second one. The problems encountered by farmer include unpredictable price and unavailability of stan.dard price, while the low product quality problem is encountered by first level trader. The retailers face the product handling difficulties before selling.